2017
DOI: 10.1016/j.snb.2016.11.108
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical sensor based on reduced graphene oxide/gold nanoparticles modified electrode for determination of iron in coastal waters

Abstract: a b s t r a c tAn electrochemical sensor based on reduced graphene oxide (rGO) and gold nanoparticles (AuNPs) modified electrode was utilized for determination of trace iron in coastal waters with the aid of the iron complexing ligand 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP). 5-Br-PADAP reacted with iron in short chelating reaction time (<3 min). rGO as a support provided large specific surface area for AuNPs, which would facilitate the electrochemical reduction of Fe(III)-5-Br-PADAP. Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Therefore, the development of an effective sensing system for selective and sensitive analysis of Fe 3+ ions is of great significance for practical applications. To date, a variety of well-established methods for the detection of Fe 3+ ions have been reported, such as inductively coupled plasma mass spectrometry (ICP-MS) [17], spectrophotometry [18], atomic absorption spectrometry (AAS) [19], and electrochemical methods [20]. However, these methods have their own limitations, for example, highly specialized instruments with complicated procedures that involve time-consuming analytical processes and high cost [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of an effective sensing system for selective and sensitive analysis of Fe 3+ ions is of great significance for practical applications. To date, a variety of well-established methods for the detection of Fe 3+ ions have been reported, such as inductively coupled plasma mass spectrometry (ICP-MS) [17], spectrophotometry [18], atomic absorption spectrometry (AAS) [19], and electrochemical methods [20]. However, these methods have their own limitations, for example, highly specialized instruments with complicated procedures that involve time-consuming analytical processes and high cost [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a gold electrode was used as a working electrode 35 and 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) was used as a Fe complexing agent with a short chelating reaction time (<3 min) 36 38 . To further validate this method and investigate Fe biogeochemistry in coastal waters, the concentration and distribution of total Fe (TFe, acidified, <0.45 μm filtered, UV-digested for 30 minutes) and acidified dissolved Fe (ADFe, acidified, <0.45 μm filtered) in local coastal Dagujia River (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their stable uniform surface capable of further functionalization leading to their increased sensitivity and selectivity, AuNPs of small size are used in electrochemical sensors [ 104 ]. It has been demonstrated that hybridizing AuNPs with conductive materials such as; rGO [ 105 ] and nitrogen-doped graphene [ 106 ], amongst others, can enhance the performance for the electrochemical detection. However, such hybridization often involves immobilizing the AuNPs with aptamers [ 107 ] or capping the NPs with capping agents in order to reduce the agglomeration of the nanoparticles [ 108 ].…”
Section: Nanocomposites In Electrochemical Sensors For Trace Metalmentioning
confidence: 99%